2020
DOI: 10.3389/fcell.2020.00429
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC01134 Promotes Hepatocellular Carcinoma Metastasis via Activating AKT1S1 and NF-κB Signaling

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies with poor outcomes. The main causes of HCC-related deaths are recurrence and metastasis. Long noncoding RNAs (lncRNAs) are recently identified as critical regulators in cancers. However, the lncRNAs involved in HCC recurrence and metastasis are poorly understood. In this study, via analyzing The Cancer Genome Atlas Liver Hepatocellular Carcinoma dataset, we identified a novel lncRNA LINC01134, which is highly expressed in HCC tissues and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
(70 reference statements)
4
20
0
Order By: Relevance
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that AKT1S1 was the most important component of the cigarette smoke exposure-related gene signature, here we observed signi cantly NNK-promoted AKT1S1 expression, which was accord with some reports that elevated AKT1S1 expression in cancer cells and could contribute to tumor metastasis 17,25 . AKT1S1 has been identi ed as an inhibitor of the mTOR complex 1, and can be phosphorylated by AKT, and ultimately releases mTOR complex 1; AKT1S1 phosphorylation state could predict hyperactivation of the AKT-mTOR pathway in multiple cancer cell types 9 .…”
Section: Discussionsupporting
confidence: 92%
“…Through compared the gene expression patterns in KIRC and normal kidney tissues, we found nine genes were not inconsistent with the ndings in RCC cells with NNK exposure. Next, the survival analysis indicated that cigarette smoke exposure-reduced genes ANKRD12, CYB5A, ECHDC3, DCN, HOXC10 and cigarette smoke exposure-promoted gene AKT1S1 showed the positive and negative relationship with overall survival in KIRC, which was accord with some studies that decreased ANKRD12 and CYB5A and increased AKT1S1 expression show a higher frequency of tumor metastasis and are indicators of increased risk of tumor progression [15][16][17] . Though cigarette smoke exposure-reduced DCN was found to be negative prognostic factor in KIRC, increasing evidences indicate that lack of DCN expression has been regarded as an indicator of tumor metastasis 18 .…”
Section: Discussionsupporting
confidence: 75%
“…The lncRNA is a novel kind of noncoding RNA, which is at least 200 nucleotides in length. The lncRNAs may participate in the progression of various diseases, especially malignant tumors [12][13][14][15][16][17] . The lncRNAs, as important tumor gene regulators, effect tumor biological behavior, transcriptional regulation, and post-transcriptional regulation [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%